1982
DOI: 10.1161/01.hyp.4.6.789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate salt restriction on intralymphocytic sodium and pressor response to stress in borderline hypertension.

Abstract: SUMMARY The effects of a moderate dietary salt restriction on intralymphocytic sodium content and pressor response to stress (mental arithmetic, handgrip, and bicycle exercise) were tested in 25 young subjects with borderline hypertension. The study was performed by a randomized, cross-over, within-patient, experimental design. Diet did not significantly reduce blood pressure at rest but did so significantly in both systolic and diastolic blood pressure during stress and exercise. Variations in diastolic blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 36 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…19 Esler et al 38 showed recently that untreated hypertensive patients on a free diet responded to mental arithmetic testing with increases of both total (70%) and cardiac (200%) NE spillover rates, whereas mean arterial pressure and heart rate elevations corresponded closely to the present ones. The explanation for the difference in NE spillover rates in the two studies from the same laboratory is unclear.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…19 Esler et al 38 showed recently that untreated hypertensive patients on a free diet responded to mental arithmetic testing with increases of both total (70%) and cardiac (200%) NE spillover rates, whereas mean arterial pressure and heart rate elevations corresponded closely to the present ones. The explanation for the difference in NE spillover rates in the two studies from the same laboratory is unclear.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, it has been suggested that pressor responses to mental arithmetic are reduced in hypertensive patients as a consequence of a low sodium diet. 19 Blood pressure and heart rate responses as well as cardiac NE spillover measurements were therefore analyzed during rest and arithmetic tests to validate whether normotensive healthy subjects fed a low sodium diet were less responsive with regard to sympathetic activation.…”
mentioning
confidence: 99%
“…It may well be that efflux, as measured by Morgan, et al, and SLC respond in different ways to changes in Na balance. Working with lymphocytes, Ambrosioni et al 13 found a significant decrease in Na concentration when a diet containing 6 to 10 g NaCl/day was switched to a diet supplying 3 to 5 g. The five participants were borderline hypertensives aged 14 to 31 years; the experimental period lasted 6 weeks. No change in BP was observed.…”
Section: Discussionmentioning
confidence: 99%
“…RCT withdrawn, by outcome: n=0 RCT excluded, with reasons: -duration <2 weeks: n=54 -co-intervention(s): n=25 -duplicate publication: n=11 -conducted in patients or pregnant women: n=7 -non-placebo control group: n=5 -lack of (appropriate) BP data: n=3 Data on body weight (initial level and change) of the trial population could not be retrieved for 11 sodium trials (28%) 21,22,24,28,30,35,40,41,46,57,58 and 7 potassium trials (26%) 35,40,61,66,67,73,76 Data on body mass index were missing for 80% of the trials and could therefore not be taken into account in the analysis.…”
Section: Data Extractionmentioning
confidence: 99%